Aktualisasi Pendidikan Agama dan Sains dalam Character Building Peserta Didik di Sekolah dan Madrasah - Mansir, Firman (J-PAI: Jurnal Pendidikan Agama Islam, 2021)
This research was conducted to analyse what methods are effective in analysing the Role of Religion and Science Education in Forming Student Character Building. Basically, learning is influenced by the determination of the selection of the method used. Islamic religious education and science are different lessons so that as educators need to channel their creativity in delivering material. In this research, the writer used literature review method. So that the results of the study refer to methods that are effectively used. In the analysis of the role of religion and science education in shaping the character building of students. The result of this research is an effective method that can be used by educators in the role of religious education and science. In the formation of character building is the mix method, namely the problem-solving method, the inquiry method and the Discovery method.